O fomento às produções culturais periféricas, o caso das rodas culturais do Estado do Rio de Janeiro - Nunes, Denilson Ribeiro de Sena (2018)
The State of Rio de Janeiro has experienced a deterioration in its economy, with a reflection on the increase of unemployment and the reduction of investments in the social area, accentuating the vulnerability of the poorest sections of the population of Rio de Janeiro. On the other hand, this population is known for its great capacity for cultural creation, even with scarce resources, such as the great offer of cultural products and services originating in poor communities, which is an alternative for the creation of employment and income for this layer of the population. However, it should be noted that R$ 1.02 billion of resources destined to cultural development under the Rouanet Law, the main instrument for the promotion of Brazilian culture, were not used in the period from 2013 to 2017. In addition, it was verified that only 3.20% of the projects approved in the same period were captained by cultural productions located in peripheral regions such as favelas and localities with the same socioeconomic characteristics. In view of this scenario, this dissertation aims to reveal updated information on the investment of cultural development resources in peripheral regions in the State of Rio de Janeiro, to investigate the reasons that prevent the cultural productions located in these regions from obtaining investments in percentages more relevant than those above. It is also intended to propose ways for this framework to be reversed, integrating cultural producers peripheral to the dynamics of the culture economy. Therefore, the question is: Why are cultural productions located in peripheral regions of the State of Rio de Janeiro unsuccessful in attracting resources destined to the promotion of culture under the Rouanet Law in more expressive percentages? The hypothesis is that: (i) the lack of knowledge and skills in regulatory frameworks and management techniques found in peripheral cultural producers is an obstacle to access to resources; and (ii) the regulatory framework for the promotion of culture has not been designed (or is not currently appropriate) to foster cultural producers in this segment. In order to take account of the objective proposed in this work, data are collected on the investment of resources of the Rouanet Law based on information contained in the database of the Ministry of Culture and fieldwork is carried out together with representatives of the Cultural Rhodes of the Hip Hop Movement, a vibrant and popular artistic manifestation of the State of Rio de Janeiro. Next, an exhibition on the regulatory framework of culture, which includes the Public Policies of Culture, the Rouanet Law and other legal instruments, will be made, which will allow to evaluate the mechanisms of development according to their skills for the development of productions in the peripheries. It is concluded that there is a need to adopt regulatory alternatives that will improve the instruments of development so that cultural producers located in peripheral regions develop and insert themselves in the cultural sector in a sustainable way.